Highly Pathogenic Avian Influenza Clade 2.3.4.4b Subtype H5N8 Virus Isolated from Mandarin Duck in South Korea, 2020 - Sol Jeong; Dong-Hun Lee; Jung-Hoon Kwon; Yu-Jin Kim; Sun-Hak Lee; Andrew Y. Cho; Tae-Hyeon Kim; Jung-Eun Park; Song-I Lee; Chang-Seon Song (Viruses, 2020)
In October 2020, a highly pathogenic avian influenza (HPAI) subtype H5N8 virus was identified from a fecal sample of a wild mandarin duck (Aix galericulata) in South Korea. We sequenced all eight genome segments of the virus, designated as A/Mandarin duck/Korea/K20-551-4/2020(H5N8), and conducted genetic characterization and comparative phylogenetic analysis to track its origin. Genome sequencing and phylogenetic analysis show that the hemagglutinin gene belongs to H5 clade 2.3.4.4 subgroup B. All genes share high levels of nucleotide identity with H5N8 HPAI viruses identified from Europe during early 2020. Enhanced active surveillance in wild and domestic birds is needed to monitor the introduction and spread of HPAI via wild birds and to inform the design of improved prevention and control strategies.